Versican in the Developing Brain: Lamina-Specific Expression in Interneuronal Subsets and Role in Presynaptic Maturation - Yamagata, Masahito (J Neurosci, 2005)
Chondroitin sulfate proteoglycans (CSPGs) of the extracellular matrix help stabilize synaptic connections in the postnatal brain and impede regeneration after injury. Here, we show that a CSPG of the lectican family, versican, also promotes presynaptic maturation in the developing brain. In the embryonic chick optic tectum, versican is expressed selectively by subsets of interneurons confined to the retinorecipient laminae, in which retinal axons arborize and form synapses. It is a major receptor for the Vicia villosa B(4) lectin (VVA), shown previously to inhibit invasion of the retinorecipient lamina by retinal axons (Inoue and Sanes, 1997). In vitro, versican promotes enlargement of presynaptic varicosities in retinal axons. Depletion of versican in ovo, by RNA interference, results in retinal arbors with smaller than normal varicosities. We propose that versican provides a lamina-specific cue for presynaptic maturation and discuss the related but distinct effects of versican depletion and VVA blockade.